Satisfacción del usuario hospitalizado en relación a cuidados de enfermería, servicio de clínica Hospital Isidro Ayora - Medina Pérez, Yadira Abigail (2015)
The new approaches to health management on user satisfaction expose that provide quality means correspond to expectations of the users, which is why the failure to provide quality nursing care, brings problems for users with care, bringing consequences for their health, generating long treatments, prolonged hospitalization and increased dissatisfaction with the image and economy of health institutions. The purpose of this study was to evaluate the satisfaction hospitalized in connection with nursing care; identifying user satisfaction regarding the courtesy with which he has been treated by the nursing staff; determine user satisfaction regarding the confidence generated by the nursing staff; identifying user satisfaction regarding communication by the nursing staff; measuring user satisfaction with regard to respect for his treatment by the nursing staff; discover user satisfaction regarding the appropriateness of care received from the nursing staff; detect user satisfaction regarding the safety of care received from the nursing staff, a proposal that was developed as a transversal descriptive research, it was used for data collection questionnaire CARE-Q or satisfaction scale of care, universe was composed hospitalized in clinical service and the sample was thirty-six users hospitalized in the Clinical Hospital "Isidro Ayora" users. The results indicate that users expressed a medium level of satisfaction with nursing care. Keywords: Satisfaction; Nursing care.